The Influence Of Training And Quality Of Human Resources On Employee Performance In The Education And Culture Office Of Lampung Province - Prasetya, Ade Indra; Josiah , Trisnowati (Universitas Dehasen Bengkulu, 2025)
The rapid dynamics of global development today, which is full of competition, has triggered changes in various areas of life as a consequence of the rapid development of science and technology (Science and Technology). The acceleration of science and technology has had a significant impact on all aspects of society, including the organizational segment. In line with the changes that are occurring, it is necessary to prepare regional governments in terms of Human Resources (HR), especially in the field of personnel management, to support the role and function of regional governments as subjects and objects of regional services and development. Realizing the importance of the HR element in an organization, it is appropriate to say that people are the most valuable asset and have a direct impact on the organization compared to other resources. The current direction of national development is focused on the importance of improving employee performance. This can be achieved by providing education and training for employees in the hope of equipping them with abilities and skills appropriate to their roles and functions. However, the reality shows that these efforts have not been able to completely change the image of employees who are oriented towards a productive work paradigm. The aim of this research is to determine: 1. The effect of training on employee performance 2. The effect of HR quality on employee performance 3. The effect of training and HR quality together on the performance of employees of the Education and Culture Office of Lampung Province. This research uses a quantitative descriptive research method, namely a research method that uses data in the form of numbers to analyze the facts found which aims to determine the relationship between variables in a population. The analysis used is simple and multiple regression. This research used 72 respondents. Based on the results of data analysis, the hypothesis answer was found as follows; There is an influence of Training (X1) on employee performance (Y) at the Lampung Province Education and Culture Office, with an influence level (R-square) of 65.6%. There is an influence of HR quality on employee performance at the Education and Culture Office of Lampung Province with an influence level of 60%. There is an influence of Training and HR Quality together on employee performance at the Education and Culture Office of Lampung Province, with an influence level of 72%.